The American Society of Maxillofacial Surgery Preceptorship Program. Issue 4 (June 2015) - Papay, Francis; Taub, Peter J.; Doumit, Gaby; Flores, Roberto L.; Kuang, Anna A.; Mlynek, Karolina; Tadisina, Kashyap K.; Gharb, Bahar Bassiri
<x xml:space="preserve">Abstract</x> Abstract One of the main goals of the American Society of Maxillofacial Surgery (ASMS) is to develop educational programs that increase expertise in maxillofacial surgery. We describe the outline of the new ASMS Preceptorship Program, a collective effort by ASMS members to increase access to all areas of maxillofacial surgery. Furthermore, we discuss the original survey pertinent to the development of this program, the results of the survey, and specifics regarding the structure of the program. We hope for the preceptorship program to be an excellent resource for members to mentor one another, develop intellectual and academic curiosity, provide avenues for collaboration, and further the ASMS's role in shaping maxillofacial surgery into the future.